The EFFECT OF REGIONAL TAXES, REGIONAL LEVIES, GENERAL ALLOCATION FUNDS, SPECIAL ALLOCATION FUNDS ON CAPITAL EXPENDITURES IN REGENCIES/CITIES IN WEST JAVA PROVINCE 2014 – 2021 - Berliani, Kartika (Journal of Accounting Inaba, 2022)
This study aims to determine whether Regional Taxes, Regional Levies, General Allocation Funds and Special Allocation Funds affect Capital Expenditures in Regencies/Cities in West Java Province. The population and sample of this research are districts/cities in West Java Province. This study aims to analyze the effect of Regional Taxes, Regional Levies, General Allocation Funds, and Special Allocation Funds on Regional Expenditures. Regional expenditure has an important role in running the government system, namely to improve public welfare and as a form of good governance. In this study using multiple linear regression analysis using data obtained from the summary of the 2014 to 2021 regional budget realization reports with the SAP format published at the Central Statistics Agency of West Java Province. The results of the study partially show that Regional Taxes, General Allocation Funds and Special Allocation Funds have no effect on capital expenditures. Regional levies, and General Allocation Funds have a significant positive effect on Capital Expenditures. Meanwhile, regional levies have an effect on capital expenditures. Simultaneously, Regional Taxes, Regional Levies, General Allocation Funds and Special Allocation Funds affect Capital Expenditures.